The Role of Gender in Agent Banking : Evidence from the Democratic Republic of Congo - Chamboko, Richard; Cull, Robert; Gine, Xavier; Heitmann, Soren; Reitzug, Fabian; Van Der Westhuizen, Morne (World Bank, Washington, DC, 2020)
This paper uses a unique data set with 1.1 million customer transactions from a microfinance institution in the Democratic Republic of Congo from 2017 to 2018. The paper provides evidence of assortative gender matching in agent banking transactions, as clients prefer to transact with agents of their own gender. Female clients show a robust preference for female agents even when they are less available, particularly when making high-value transactions and when they have higher account balances. The underrepresentation of female agents may contribute to the persistent gender gap in financial access and usage.